Homeless veterans in the Caribbean: Profile and housing failure (Revista Puertorriqueña de Psicologia, 2021)
This research assesses sociodemographic, psychosocial, and military characteristics and their role in homelessness programs readmission to provide a profile of the Caribbean Homeless Veteran of the U.S. military. We evaluated 620 healthcare records of veterans who requested services at the Homeless Program of the VA Caribbean Healthcare System from 2005 to 2014. Statistical analyses consisted of Chi square, Fisher’s exact test, Wilcoxon-Rank Sum tests, and generalized linear models of regression with Poisson distribution. Homeless veterans were characterized by being male, serving in the Army, having low social support, poor house affordability, extreme poverty, unemployment, and psychiatric disorders. Veterans from Operation Iraqi Freedom, Operation Enduring Freedom, and Operation New Dawn conflicts exhibited more readmission prevalence risk ratio overall and when adjusted for all factors than veterans of previous conflicts. Psychosocial factors such as substance use, social isolation, legal problems, and psychiatric disorders were identified in the readmission process. Results suggest assistance beyond housing is needed to end veteran homelessness.